Effect of Cassave leaf flavonoid extract on TNF-α expressions in rat models suffering from periodontitis - Zahara Meilawaty; Banun Kusumawardani (Universitas Airlangga, 2016)
Background: Bacteria playing a role in periodontitis are Gram-negative anaerobic bacteria that can release endotoxin or lipopolysaccharide (LPS). LPS acts as a stimulus to a variety of host cells that can stimulate expression of pro-inflammatory cytokines in periodontal disease, such as IL-1α, IL-1β, and TNF-α. Increased TNF-α then can lead to periodontal tissue destruction. Furthermore, cassava leaves have many health benefits due to flavonoid organic compound contained, known to possess anti-inflammatory activity are used as a medicine. Purpose: This study aimed to determine the effect of cassava leaf flavonoid extract as a basic ingredient of anti-inflammatory gel on TNF-α expression in Wistar rats suffering from periodontitis induced with Escherichia coli (E. coli) LPS. Method: This study used 24 male Wistar rats. Those rats were divided into six groups. Group 1 consisted of four rats induced with E. coli LPS for 2 weeks, and then decapitation was performed on day 3. Group 2 consisted of four rats induced with E. coli LPS for 2 weeks, and then decapitation was conducted on day 7. Group 3 consisted of four rats induced with E. coli LPS for 2 weeks, treated with the topical cassava leaf flavonoid extract gel (Manihot esculenta) at a concentration of 25%, and then decapitation was performed on day 3. Group 4 consisted of four rats induced with E. coli LPS for 2 weeks, treated with the topical cassava leaf flavonoid extract gel (Manihot esculenta) at a concentration of 25%, and then decapitation was conducted on day 7. Group 5 consisted of four rats induced with E. coli LPS for 2 weeks, treated with the topical cassava leaf flavonoid extract gel (Manihot esculenta) at a concentration of 50%, and then decapitation was performed on day 3. And, group 6 consisted of four rats induced with E. coli LPS for 2 weeks, treated with the topical Cassava leaf flavonoid extract gel (Manihot esculenta) at a concentration of 50%, and then decapitation was conducted on day 7. The topical Cassava leaf flavonoid extract gel was inserted into gingival sulcus on the first right molar of their lower jaw by using a blunted syringe needle. The gel was given two times a day for 7 days. Result: The expression of TNF-α in the control group was more than that in the treatment groups given the Cassava leaf flavonoid extract gel at the concentrations of 25% and 50%. The expression of TNF-α in the treatment groups given the cassava leaf flavonoid extract gel at the concentration of 50% was lower than that in the treatment groups given the cassava leaf flavonoid extract gel at the concentration of 25%. Conclusion: Cassava leaf flavonoid extract gel could be used as an anti-inflammatory gel characterized by a decrease in TNF-α expression in rat models suffering from periodontitis.